Multicultural Values in Learning Islamic Religious Education (Study at SDIT Khoiru Ummah Rejang Lebong) - Yova Atika; Eka Yanuarti (Indonesian Journal for Islamic Studies, 2023)
This research is motivated by the importance of implementing multicultural values in schools. The problem that often occurs is that schools do not turn on good multicultural education, there are lots of fights, bullying that occurs in the school environment caused by differences in ethnicity, religion, and culture. Meanwhile, researchers saw that at SD IT Khoiru Ummah, even though the students have different ethnic and cultural backgrounds, they are friends without discriminating against ethnicity or culture, respect each other, and almost never fight. This study aims to find out what are the multicultural values contained in the learning of Islamic Religious Education. The method used in this research is qualitative method. The subjects of this study were school principals, Islamic religious education teachers and Khoiru Ummah Integrated Islamic Elementary School (SDIT) students. Data collection techniques through observation, interviews, and documentation. Then the data analysis technique uses data reduction, data presentation, and conclusions or verification. The results of this study concluded that the multicultural values contained in the learning of Islamic Religious Education (PAI) are the values of tolerance, human values, values of unity and oneness, social values and values of justice.